1998
DOI: 10.1177/155005949802900110
|View full text |Cite
|
Sign up to set email alerts
|

Possible EEG Sequelae of Very Long Duration Marihuana Use: Pilot Findings from Topographic Quantitative EEG Analyses of Subjects with 15 to 24 Years of Cumulative Daily Exposure to THC

Abstract: In previous work we demonstrated and replicated a significant association between increased absolute and relative power and interhemispheric coherence of EEG alpha activity over the bilateral frontal-central cortex ("alpha hyperfrontality") in daily marihuana users as contrasted with nonusers. In this report we focused our analyses on subjects who reported smoking marihuana on a daily basis for 15 to 24 consecutive years. Compared to nonuser controls and subjects who had used marihuana on a daily basis for sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…In one pilot study, Struve et al [33] found tentative evidence that EEG abnormalities were more pronounced in longerduration cannabis users, even after adjusting for the greater age of these individuals. More striking findings were obtained by Solowij [28•], who found a significant correlation between duration of cannabis use and increased processing negativity to complex irrelevant stimuli in a selective attention task.…”
Section: Long-term Residual Effectsmentioning
confidence: 94%
“…In one pilot study, Struve et al [33] found tentative evidence that EEG abnormalities were more pronounced in longerduration cannabis users, even after adjusting for the greater age of these individuals. More striking findings were obtained by Solowij [28•], who found a significant correlation between duration of cannabis use and increased processing negativity to complex irrelevant stimuli in a selective attention task.…”
Section: Long-term Residual Effectsmentioning
confidence: 94%
“…A recent meta-analysis seems to argue against this possibility (Grant et al, 2001), as does a longitudinal population study of heavy cannabis users (Lyketsos et al, 1999) and recent data from our own laboratory (Pope et al, 2001a(Pope et al, ,b, 2002. Other studies, however, have suggested an association between lifetime cannabis exposure and electroencephalographic (Struve et al, 1998) or neuropsychologic abnormalities (Solowij, 1998). Recently, another study (Solowij et al, 2002) has reported a significant association between lifetime cannabis use and neuropsychological test performance among users seeking treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These studies (Alper et al, 1990;Noldy et al, 1994;Prichep et al, 1996;Roemer et al, 1995;Trudeau, Thuras, & Stockley, 1999) based on reasonably uniform abstinence times and employing different EEG technology and analytical approaches, have produced remarkably similar findings of alpha relative amplitude excess with delta relative amplitude deficit that is striking. Excess alpha amplitude with slowing of alpha frequency associated with chronic cannabis abuse has been reported (Struve et al, 1998). As noted, Scott and Kaiser (1998) described combining a protocol for attentional training (beta reward) with alpha-theta training in a population of participants whose primary drugs of abuse were stimulants and who had features of ADHD.…”
Section: Clinical Considerations: Comorbidities Of Sud and Implicatiomentioning
confidence: 99%